CamelliA-based simultaneous imaging of Ca2+ dynamics in subcellular compartments. Issue 4 (26th February 2022) - Guo, Jingzhe; He, Jiangman; Dehesh, Katayoon; Cui, Xinping; Yang, Zhenbiao
Abstract: As a universal second messenger, calcium (Ca 2+ ) transmits specific cellular signals via a spatiotemporal signature generated from its extracellular source and internal stores. Our knowledge of the mechanisms underlying the generation of a Ca 2+ signature is hampered by limited tools for simultaneously monitoring dynamic Ca 2+ levels in multiple subcellular compartments. To overcome the limitation and to further improve spatiotemporal resolutions, we have assembled a molecular toolset (CamelliA lines) in Arabidopsis ( Arabidopsis thaliana ) that enables simultaneous and high-resolution monitoring of Ca 2+ dynamics in multiple subcellular compartments through imaging different single-colored genetically encoded calcium indicators. We uncovered several Ca 2+ signatures in three types of Arabidopsis cells in response to internal and external cues, including rapid oscillations of cytosolic Ca 2+ and apical plasma membrane Ca 2+ influx in fast-growing Arabidopsis pollen tubes, the spatiotemporal relationship of Ca 2+ dynamics in four subcellular compartments of root epidermal cells challenged with salt, and a shockwave-like Ca 2+ wave propagating in laser-wounded leaf epidermis. These observations serve as a testimony to the wide applicability of the CamelliA lines for elucidating the subcellular sources contributing to the Ca 2+ signatures in plants. Abstract : A toolset for simultaneous imaging of Ca 2+ dynamics in subcellular compartments has uncovered unrecognized Ca 2+ signatures in Arabidopsis cells in response to developmental and external cues.